The Influence of Income, Number of Family members, and Education on Household Consumption in Ngagel Rejo Village - Cyntya Dwi Permata; Sishadiyati (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to determine the effect of income, number of family members, and education on household consumption expenditure in Ngagel Rejo Village, Surabaya. This research was conducted using a quantitative approach and analyzed using multiple linear regression. Data were obtained from 150 respondents selected based on certain criteria. The results showed that simultaneously, the three variables had a significant effect on household consumption. Separately, only income and number of family members showed a significant effect, while education did not. These results can be taken into consideration for policy formulation related to community welfare.